Perancangan Aplikasi Kamus Bahasa Daerah Nias Berbasis Android dengan Metode Rapid Application Development (RAD) Menggunakan Android Studio - Zalukhu, Desman Jaya; Karo, Panser Karo; Faizah, NM (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2023)
The purpose of this research is to design a dictionary application that can translate Nias language based on Android and can be operated on a smartphone to assist in translating Indonesian into Nias language correctly. At the development stage, Rapid Application Development (RAD) is used. Based on the research that has been done, it can be concluded that the Nias-Indonesian Dictionary application has a very impact and received a positive response from the surrounding community, especially among the people in the interior, because this is the first mobile-based application where the process of using it is simpler and more flexible. This system can be used as a medium of learning and communication for the surrounding community. So that the preservation of Nias language and culture is maintained.